Knowledge and Attitude towards Cardiopulmonary Resuscitation among Students of a Dental College - Pun, Dilli Bahadur; Thapa, Bobby; Shrestha, Prashanna; Chaudhary, Sonam; Pandey, Nashib; Chaurasia, Lokeshwar (Janaki Medical College Journal of Medical Science, 2020)
Background and Objectives: Survival after cardiopulmonary arrest depends on early and effective cardiopulmonary resuscitation (CPR). Demand for courses of basic life support (BLS)/CPR is increasing worldwide. Till date, there have been little reports regarding CPR knowledge and attitude among the Nepalese dental health personnel. This study aimed to assess the knowledge and attitude towards CPR among undergraduate dental students, interns and postgraduate residents studying at Kantipur Dental College and Teaching Hospital (KDCH), Kathmandu, Nepal. Material and Methods: A descriptive cross-sectional study was conducted among 243 dental students studying at KDCH. Data was collected through a self -administered semi-structured questionnaire. Collected data was organized, recorded, coded and then analyzed using Statistical Package of Social Science (SPSS) version 16. Descriptive statistics was used to compute mean, percentile, standard deviation and one way ANOVA test was done to compare the mean knowledge score between different academic levels of the students at 95% level of significance. Results: The mean knowledge and attitude score towards CPR among the dental students was 8.05±2.85 and 4.63±0.51 respectively. Out of total students, only few (5.8%) had adequate knowledge whereas all (100%) had a positive attitude towards CPR. The mean score for the pre-clinical students (7.26 ±2.38) was significantly (p=0.001) lower than clinical students (8.44 ±3.23), interns and residents (8.85 ±2.54). Conclusion: The present study showed inadequate knowledge regarding CPR among dental students of different academic levels but they have a positive attitude towards it. The integration of CPR in the early year of the curriculum along with regular training of CPR in succeeding years will enhance their knowledge.